Providing Context to the Engagement-Behavior Linkage: A Facet-Level Examination. Issue 1 (1st January 2022) - Winton, Steven; Cornelius, Andrea; Grawitch, Matthew
ABSTRACT: This two-study investigation utilized two popular engagement measures, the Utrecht Work Engagement Scale (UWES) and the Shirom-Melamed Vigor Measure (SMVM), to explore how facets of state-affective experience related to discrete behavioral outcomes by distinguishing proactive from contextual and in-role behavior. Two independent samples of working adults were used to test various structural models across Study 1 and Study 2, with Study 2 examining behaviors at different time lags (i.e., one-week and one-month). The findings indicated that aspects of engagement signifying a cognitive immersion in work may have unique associations with proactive behaviors such as taking charge. We concluded that these findings provide a deeper understanding of how facets of engagement relate to distinct performance outcomes, as well as how these relationships hold across time.